2015
DOI: 10.1371/journal.pone.0117661
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Evaluation of the Histological Grade of Hepatocellular Carcinoma with Diffusion-Weighted Imaging: A Meta-Analysis

Abstract: ObjectiveTo evaluate the diagnostic performance of diffusion-weighted imaging (DWI) in the preoperative prediction of the histological grade of hepatocellular carcinoma (HCC).Materials and MethodsA comprehensive literature search was performed in several authoritative databases to identify relevant articles. QUADAS-2 was used to assess the quality of included studies. Data were extracted to calculate the pooled sensitivity, specificity, positive likelihood ratio (PLR) and negative likelihood ratio (NLR). Summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
4
24
0
Order By: Relevance
“…Choi et al have shown that HCCs with atypical enhancement pattern and iso-to-hyperintensity on contrast-enhanced MRI were associated with lower tumor grade and better prognosis after surgical resection [16]. Moreover, a recent meta-analysis showed that diffusion-weighted imaging (DWI) has a high diagnostic accuracy in the preoperative prediction of well and poorly differentiated HCC (AUC = 0.93 and 0.85, respectively) [20]. Venkatesh et al have shown that MRE is feasible for measuring liver tumor stiffness (kPa) and is more accurate than diffusion-weighted imaging (DWI) for differentiating benign and malignant focal liver lesions [23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al have shown that HCCs with atypical enhancement pattern and iso-to-hyperintensity on contrast-enhanced MRI were associated with lower tumor grade and better prognosis after surgical resection [16]. Moreover, a recent meta-analysis showed that diffusion-weighted imaging (DWI) has a high diagnostic accuracy in the preoperative prediction of well and poorly differentiated HCC (AUC = 0.93 and 0.85, respectively) [20]. Venkatesh et al have shown that MRE is feasible for measuring liver tumor stiffness (kPa) and is more accurate than diffusion-weighted imaging (DWI) for differentiating benign and malignant focal liver lesions [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…As such, imaging biomarkers may provide important surrogate HCC tumor biologic, pathologic and ultimately prognostic information for patient stratification in clinical trials and clinical practice [14]. Various imaging features by CT, MRI and PET have been proposed as imaging biomarkers for HCC but none have been translated into routine clinical practice or clinical trials for HCC [1520]. Magnetic resonance elastography (MRE) is a noninvasive MRI based technique for quantitatively assessing the mechanical properties of tissues and has been used clinically most extensively in the liver as a quantitative tool for diagnosing and staging liver fibrosis [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…20 Most commonly, HCC shows restriction of water diffusion, paralleling degree of cellularity and dedifferentiation. Furthermore, a recent meta-analysis concluded that DWI had excellent and moderately high diagnostic accuracy for the prediction of well-differentiated versus poorly differentiated HCC, 21 although overlap remains between different histologic grades. 22 Recently, IVIM-derived D values of HCC showed significantly better diagnostic performance than ADC values in differentiating high-grade from low-grade HCC.…”
Section: Diffusion-weighted Mr Imagingmentioning
confidence: 99%
“…A meta‐analysis of using DWI to assess the histological grade of HCC was performed by Chen et al in 2015, and the authors concluded that the pooled sensitivity and specificity of DWI were 54% and 90% for discriminating well‐differentiated HCC and 84% and 48% for discriminating poorly differentiated HCC, respectively. However, seven of the 11 included DWI studies were quantitative and the others were qualitative, which can inevitably cause between‐study heterogeneity and affect the accuracy of the research results.…”
mentioning
confidence: 99%